Age, educational level and consumption of medical care: evidence from Malaysia - Cheah, Yong Kang; Abdul Adzis, Azira; Abu Bakar, Juhaida; Tang, Chor Foon; Lim, Hock Kuang; Kee, Chee Cheong (Malaysian Public Health Physicians' Association Publication, 2020)
The present study examines age and educational level determinants of the consumption of medical care using data from Malaysia. A nationally representative data with a large sample size (n = 14838) was used for analyses.Several important findings are noteworthy. First, age and educational level are positively associated with the consumption of medical care. Second, the impact of educational level on the consumption of medical care varies across age.Third, there is no diminishing marginal effect of educational level on the consumption of medical care.Findings of the present study suggest that age and educational level play an important role in determining the consumption of medical care.When designing policies to improve population well-being, consideration should be given to the effects of age and educational level on the consumption of medical care.It is important for policymakers to understand which age group and educational level of people are more or less likely to use medical care.The present study offers a better understanding of the effects of age and educational level on the consumption of medical care and assists policymakers in developing more effective intervention measures to improve population well-being.